Screening of Metarhizium anisopliae (Metsch.) Sorok. strains against Mahanarva fimbriolata (Stal, 1854) (Hemiptera: Cercopidae) - Macedo, Daniella; Alves, Sérgio Batist; Vieira, Solange Aparecida (Semina: Ciências Agrárias, 2006)
The mechanized harvest of sugarcane results in accumulation of mulch on the soil and promotes favorable temperature and moist to development of sugarcane root spittlebug, Mahanarva fimbriolata (Stal, 1854) (Hemiptera: Cercopidae). High populations of this pest causes serious damages to plants and high costs with insecticides. This research work tested strains of Metarhizium anisopliae (Metsch.) Sorok. pathogenic to sugarcane root spittlebug using a new methodology. The selection was carried out in laboratory conditions. Nymphs were sprayed with 2 mL of a suspension containing 5x107 conidia/mL and maintained in roots of sugarcane. The corrected mortality was evaluated five days after pulverization and ranged from 10.5 to 60% and the more pathogenic strains caused mortality from 46.5 to 59.7%.